FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENERIMAAN AUDITOR PADA KANTOR AKUNTAN PUBLIK DI MAKASSAR - Ibrahim Ibrahim (AkMen JURNAL ILMIAH, 2017)
This study aimed (1) to determine if the first impression (the effect of appearance) positive influence on admissions decisions auditor in public accounting firm in Makassar. (2) To determine whether the positive effect on the physical attraction admissions decisions auditor in public accounting firm in Makassar. (3) To determine whether the inter-personal interests positive influence on admissions decisions auditor in public accounting firm in Makassar. (4) To determine whether a common perception of positive influence on admissions decisions padaKantor auditor Public Accountants in Makassar. (5) Untukmengetahui whethersubjective qualification positive influence on admissions decisions auditor in public accounting firm in Makassar. (6) To determine whether an objective qualification positive influence on admissions decisions auditor in public accounting firm in Makassar. (7) To determine whether gender positive influence on admissions decisions auditor in public accounting firm in Makassar. (8) To determine whether the positive effect on the competence of the auditor'sdecision on acceptance of public accounting firm in Makassar. whereas the method of analysis used in this study is menggunakanmetode analisislogistic regression (logistic regression). Logistic regression does not require normality test, heteroskedasitas, and classical assumption on the dependent variable. The results of this study are the independent variables There are 4 positive influence on admissions decisions is a common perception and objective qualifications, gender, and kompetensi.Ada 4 independent variable that is not a positive influence on admissions decisions auditor that is the first impression, physical attraction, interest among private and subjective qualifications.